Pengaruh Tekanan Karyawan, Struktur Kepemilikan dan Leverage terhadap Penjaminan Laporan Keberlanjutan - Fiony Melenia; Nurzi Sebrina (Universitas Negeri Padang, 2024)
This study aims to analyze the effect of employee pressure, ownership structure and leverage on the sustainability reports assurance. The dependent variable is sustainability report assurance with its measurement divided into four categories. While the independent variables are employee pressure, institutional ownership, majority ownership and leverage. The employee pressure variable is measured by the logaritma natural (Ln) of the number of employees. Institutional ownership variable is measured by comparing the number of shares owned by the institution and the number of outstanding shares. The majority ownership variable is measured by comparing the number of shares owned by the majority and the number of outstanding shares. The leverage variable is measured by comparing the company's total debt and total assets. This study uses a control variable, namely profitability. The research population is companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. Determination of the research sample was carried out by purposive sampling technique and obtained a sample of 43 companies with a total of 215 observations. The analysis technique used is multiple linear regression analysis. The results indicate that employee pressure, majority ownership and leverage do not have a significantly positive effect on sustainability report assurance. Institutional ownership has a negative and significant effect on sustainability reports assurance.